Comparison of National and International Standards of Good Egg Production Practices - Sousa, G. P. [UNESP]; Pereira, D. F. [UNESP]; Watanabe, K. [UNESP]; Cataneo, P. F. [UNESP] (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2016)
Egg production is an important economic activity in Brazil, with about 697 million eggs produced annually. The conventional cage system is commonly used for egg production. However, there has been a growing concern for the welfare of laying hens around the world. In this context, many countries have issued laws, protocols, and other normative technical specifications to ensure the welfare of layers. This study aims at identifying similarities and differences between international standards and Brazilian protocols using the Comparative Law perspective. This article reports an analytical study of selected protocols, performing three analyses using the Comparative Law method. The research concludes that some items of the Brazilian protocols of good egg production practices, such as farm inspection, treatment of diseases, temperature, ventilation, beak trimming, feed and water supply, correspond to international specifications, whereas others, such as housing, freedom movement, use of equipment, and transport, are less strict.
Keywords: Egg production; animal welfare; Comparative Law; legislation